Both cardiomyocyte and endothelial cell Nox4 mediate protection against hemodynamic overload-induced remodelling. Issue 3 (13th October 2017) - Zhang, Min; Mongue-Din, Heloise; Martin, Daniel; Catibog, Norman; Smyrnias, Ioannis; Zhang, Xiaohong; Yu, Bin; Wang, Minshu; Brandes, Ralf P; Schröder, Katrin; Shah, Ajay M
Abstract: Aims: NADPH oxidase-4 (Nox4) is an important reactive oxygen species (ROS) source that is upregulated in the haemodynamically overloaded heart. Our previous studies using global Nox4 knockout (Nox4KO) mice demonstrated a protective role of Nox4 during chronic abdominal aortic banding, involving a paracrine enhancement of myocardial capillary density. However, other authors who studied cardiac-specific Nox4KO mice reported detrimental effects of Nox4 in response to transverse aortic constriction (TAC). It has been speculated that these divergent results are due to cell-specific actions of Nox4 (i.e. cardiomyocyte Nox4 detrimental but endothelial Nox4 beneficial) and/or differences in the model of pressure overload (i.e. abdominal banding vs. TAC). This study aimed to (i) investigate whether the effects of Nox4 on pressure overload-induced cardiac remodelling vary according to the pressure overload model and (ii) compare the roles of cardiomyocyte vs. endothelial cell Nox4. Methods and results: Global Nox4KO mice subjected to TAC developed worse cardiac remodelling and contractile dysfunction than wild-type littermates, consistent with our previous results with abdominal aortic banding. Next, we generated inducible cardiomyocyte-specific Nox4 KO mice (Cardio-Nox4KO) and endothelial-specific Nox4 KO mice (Endo-Nox4KO) and studied their responses to pressure overload. Both Cardio-Nox4KO and Endo-Nox4KO developed worse pressure overload-induced cardiac remodelling and dysfunction than wild-type littermates, associated with significant decrease in protein levels of HIF1α and VEGF and impairment of myocardial capillarization. Conclusions: Cardiomyocyte as well as endothelial cell Nox4 contributes to protection against chronic hemodynamic overload-induced cardiac remodelling, at least in part through common effects on myocardial capillary density.